Improved Fecal DNA Test for Colorectal Cancer Screening - Itzkowitz, Steven H.; Jandorf, Lina; Brand, Randall; Rabeneck, Linda; Schroy, Paul C.; Sontag, Stephen; Johnson, David; Skoletsky, Joel; Durkee, Kris; Markowitz, Sanford; Shuber, Anthony (Clinical gastroenterology and hepatology, 2007)
Background & Aims: Fecal DNA testing has shown greater sensitivity than guaiac-based occult blood tests for noninvasive colorectal cancer (CRC) screening. The prototype assay (version 1), which analyzed 22 gene mutations and DNA integrity assay (DIA), showed a sensitivity of 52% for CRC detection and a specificity of 94% in average-risk individuals. The present study was conducted to determine the sensitivity and specificity of a second-generation assay (version 2) that uses improved DNA stabilization/isolation techniques and a new promoter methylation marker. Methods: Forty patients with CRC and 122 subjects with normal colonoscopy provided stool samples to which DNA preservation buffer was added immediately. DNA was purified using gel-based capture, and analyzed for the original panel of 22 mutations, DIA, and 2 new promoter methylation markers. Results: By using DNA that was optimally preserved and purified from stool, the sensitivity of the prototype version 1 assay increased to 72.5% because of enhanced performance of DIA. Vimentin gene methylation alone provided sensitivity and specificity of 72.5% and 86.9%, respectively. The optimal combination of vimentin methylation plus DIA resulted in 87.5% sensitivity and 82% specificity; cancers were detected regardless of stage or location. False-positive vimentin methylation was associated with older age. Conclusions: An improved fecal DNA test that incorporates only 2 markers shows much higher sensitivity for CRC. The new assay is easier to perform and should be less costly, thereby facilitating its use for noninvasive CRC screening.